Facile green synthesis of silver doped NiO nanoparticles using aloe vera latex for efficient energy storage and photocatalytic applications - S. Alfadhli; Syed Khasim; A.A.A. Darwish; Khoulod Al-nahdi; Mervat Abdelkader; Raghad Gamal; Taymour A. Hamdalla (Heliyon)
Herein, we report the biosynthesis of pure NiO and NiO nanoparticles doped with Silver (Ag@NiO NPs) 2, 4, 6, and 8 mol% from aloe vera extract by solution combustion method at 400 °C and calcined at 500 °C for 3 h. By utilizing silver-doped NiO nanoparticles synthesized with Aloe Vera latex, which not only enhances the material's properties but also promotes environmentally friendly fabrication methods. The morphological, structural elemental compositions were analysed through SEM, HRTEM, SAED, XRD and EDAX. The band gap was determined as 2.48, 2.57, 2.58, 2.60, and 2.62 eV for pure NiO, 2–8% Silver doped NiO using Kubelka-Munk plot. The photocatalytic potential of the 6 % Ag doped NiO has been explored by assessing their effectiveness in degrading fast blue (FB) dye, demonstrating significant activity at 605 nm. Remarkably, with 120 min of UV radiation, the FB dye reaches an impressive photodegradation rate of 98 %, making the dye nearly colorless. The green synthesized NPs were tested in 1 M KOH to investigate their supercapacitor performance as an effective material for electrode. The Cyclic Voltammetry (CV), the Galvanostatic charge-discharge (GCD), and the Electrochemical impedance spectroscopy (EIS) studies were conducted to determine the materials' electrochemical activity. The GCD study for 6 mol% Ag@NiO in a 3-electrode system shows a capacitance of 535 F g−1 at a current density of 1 Ag-1. 6 mol% Ag@NiO modified electrode shows excellent long-term stability, retention of more than 92 % of its initial capacitance after the operation of 2000 cycles. The important outcome of this work lies in multifunctional application of the as-synthesized materials, demonstrating their effectiveness for both efficient energy storage and improved photocatalytic performance, paving the way for sustainable and multifunctional devices.